Capturing Relatedness: Comprehensive Measures based on Secondary Data. (19th August 2015) - Nocker, Elisabeth; Bowen, Harry P.; Stadler, Christian; Matzler, Kurt
Abstract : This paper presents new measures of technological and customer‐side relatedness constructed from widely available secondary data. Relatedness is a concept central to predicting the existence and nature of a relationship between corporate diversification and firm performance. Yet, finding appropriate measures has been an ongoing struggle. The widely used SIC‐based entropy measure has low construct validity, and survey‐based measures are hard to replicate across firms and industries and over time. The measures we develop significantly outperform established measures in explaining variation in firm performance across firms and over time, and both sources of relatedness are found to be independent and significant explanations of firm performance.